Teaching the Teachers About Language Support Strategies: Effects on Young Children's Language Development - Voltmer, Katharina; Hormann, Oliver; Pietsch, Marcus; Maehler, Claudia; von Salisch, Maria (Frontiers in Psychology, 2021)
The Feeling Thinking Talking (FTT) intervention was designed because early childhood seems to be a prime time for fostering young children’s language skills. This intervention involved teaching teachers from N = 28 groups in N = 13 German kindergartens Language Support Strategies (LSS) to be used in everyday conversations with the children in their care. The FTT intervention was evaluated in a business-as-usual control group design with N = 281 children (Mage = 49.82 months, range = 33-66 months at T1, mixed SES) who were individually tested using objective tests on grammar, vocabulary and working memory before (T1) and after the FTT intervention (T2), and in a follow-up three to six months later (T3). After propensity matching was applied, multilevel models demonstrated that the children taught by the intervention group teachers made faster progress in their understanding of sentences, their application of morphological rules, and their memory for sentences when numerous covariates (child age, gender, behavioral self-regulation, multilingual upbringing, and family SES) were controlled. Results suggest that complex language processing abilities in young children can be promoted by a teacher-led intervention in elementary school. Improved language skills will further all children’s academic and social success in school.